Implementasi Pemberian Penghargaan Profesi Guru Era Kontemporer di Sekolah Dasar Islam Qurthuba Makassar: Implementation of Teacher Professional Awards in the Contemporary Era at Qurthuba Islamic Elementary School Makassar - Nur Hadika, Amaliyah; Rosdiana; Achruh, Andi (CV. Kalimasada Group, 2023)
The role of teachers in education is very strategic, even other educational resources are often meaningless if not accompanied by adequate teacher quality. Professionally qualified teachers are those who know deeply about what they teach, are proficient in effective and efficient teaching methods and have a personality. Teachers must also have good work skills and high maturity of thinking, because the professional position of teacher is a strategic position in the life and development of society. This article discusses the implementation of teacher appreciation which aims to find out: knowing the understanding of the implementation of teacher appreciation at Qurthuba Islamic Elementary School Makassar and knowing the types of teacher appreciation at Qurthuba Islamic Elementary School Makassar. This type of research is descriptive qualitative research using an educational approach, the data source in this study is 1 Qur'an teacher. This research uses observation and interviews. The data analysis method uses data presentation and conclusion drawing or verification. To test the validity of the data using triangulation. the implementation of teacher awards at Qurthuba Islamic School Makassar is an award given for achieving the best teacher assessment criteria both from the results of teacher performance and the results of peer assessment. The awards given are cash and certificates